Evaluation of Silkworm Lines against Variations in Temperature and RH for Various Parameters of Commercial Cocoon Production - Mubashar Hussain; Shakil Ahmad Khan; Muhammad Naeem; Tahir Aqil; Rizwan Khursheed; Ata ul Mohsin (Psyche: A Journal of Entomology)
Eleven inbred silkworm lines (M-101, M-103, M-104, M-107, Pak-1, Pak-3, Pak-2, Pak-4, PFI-1, PFI-2, and S-1) were evaluated for various parameters of cocoon production under different temperature and relative humidity conditions (25±1, 30±1, and 35±1 °C in combination with 55, 65, and 75% RH for three hrs during 4th and 5th instar. The experiment was laid out in factorial design with three replications. Significant variations in the performance of silkworm lines were noticed due to influence of temperature and RH treatment on 4th and 5th instar larvae. The silkworm lines performed significantly better when the larvae were reared at 25±1 °C with 70–80% RH while almost all the silkworm lines showed poor performance at higher temperature exposures for 3 hrs. Exposures to lower humidity (55%) during larval rearing in 4th and 5th instar at different temperatures (25±1, 30±1, and 35±1 °C) resulted in lowering the cocoon production. The cumulative evaluation index values for different traits showed that Pak-4 (61.42) was the best line followed by M-101 (59.15), Pak-2 (56.37), Pak-3 (52.83) PFI-I (52.62), and M-107(50.03). The study clearly underlines the importance of optimization of environmental conditions during larval rearing in relation to commercial cocoon production. The investigations strongly recommend that temperature and relative humidity in the range of 25-26 °C and 70–80%, respectively, are mandatory for excellent results of cocoon production and Pak-4, M-101, Pak-2, Pak-3, PFI-I, and M-107 were suitable for commercial rearing.